2014
DOI: 10.1021/jp508627h
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Lysine Adsorption on Fumed Silica Nanoparticles

Abstract: The adsorption of amino acids on silica surfaces has attracted considerable interest since it has a broad range of applications in various fields such as drug delivery, solid-phase peptide synthesis and biocompatible materials synthesis. In this work, we systematically study lysine adsorption on fumed silica nanoparticles with thermal analysis and solid-state NMR. Thermal-gravimetric analysis (TGA) results show that the adsorption behavior of lysine in low concentration aqueous solutions is well described b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 77 publications
5
55
0
Order By: Relevance
“…Most intensity correlations in this 2D spectrum originate from directly bound intraresidue 1 H and 13 C nuclei, which allows their assignments to specific 1 H and 13 C moieties of the lysine, tyrosine, cysteine and glycine residues of the Tyr peptide. These resonance assignments are corroborated by the solid-and solution-state NMR spectra of neat peptides and polypeptides reported in the literature [36][37][38][39][40] .…”
Section: Resultssupporting
confidence: 72%
“…Most intensity correlations in this 2D spectrum originate from directly bound intraresidue 1 H and 13 C nuclei, which allows their assignments to specific 1 H and 13 C moieties of the lysine, tyrosine, cysteine and glycine residues of the Tyr peptide. These resonance assignments are corroborated by the solid-and solution-state NMR spectra of neat peptides and polypeptides reported in the literature [36][37][38][39][40] .…”
Section: Resultssupporting
confidence: 72%
“…demonstrated that hydrogen bonds participate in the binding of peptides to titania with NMR spectroscopy . Similar involvement of hydrogen bonds can be evidenced with NMR for amino acids and peptides on silica surfaces In addition, the binding of the amino acid lysine through hydrogen bonds to silica was demonstrated by NMR spectroscopy . The binding of cysteine containing peptides to noble metal surfaces has been verified with NMR spectroscopy as well .…”
Section: Structural and Mechanistic Description Of Peptide‐surface Insupporting
confidence: 59%
“…Other destructive techniques, like induced coupled plasma, also yield the equilibrium constant by quantifying individual elements . While a determination of the binding capacity of organic molecules on inorganic surfaces is possible, the equilibrium constant K D calculated from TGA results is often higher than with other methods indicating a lower thermodynamic probability of the surface to bind the molecules but the lower sensitivity might falsify the binding constant . In several cases the analysis of the binding affinity by analysis of adsorbent in the supernatant (liquid sample) and adsorbate on the adsorber (solid sample) yielded similar results .…”
Section: Determination Of Binding Affinitiesmentioning
confidence: 99%
“…Until recently, only the structures of Au 23 (SC 6 H 11 ) 16 , Au 25 (PET) 18 , Au 25 (SEt) 18 , Au 28 (TBBT) 20 , Au 36 (SPh‐tBu) 24 , Au 38 (SR) 24 , and Au 102 (p‐MBA) 44 have been successfully determined by X‐ray crystallography. Comparing with all these techniques, nuclear magnetic resonance (NMR) spectroscopy has been demonstrated to be a universal and versatile technique for characterization of nanomaterials . One‐dimensional/multidimensional NMR spectroscopy combined with homonuclear/heteronuclear NMR spectroscopy provides considerable methods for characterizing nanostructures including purity, ligand density, and surface chemistry .…”
Section: Introductionmentioning
confidence: 99%